Enhancement of Rubella Virus Infection in Immortalized Human First-Trimester Trophoblasts Under Low-Glucose Stress Conditions - Trinh, Quang Duy; Takada, Kazuhide; Pham, Ngan Thi Kim; Takano, Chika; Namiki, Takahiro; Ikuta, Ryo; Hayashida, Shingo; Okitsu, Shoko; Ushijima, Hiroshi; Komine-Aizawa, Shihoko; Hayakawa, Satoshi (Frontiers in Microbiology, 2022)
Rubella virus (RuV) infections in pregnant women, especially first-trimester infections, can lead to congenital rubella syndrome (CRS). However, the mechanisms of fetal RuV infection are not completely understood, and it is not observed in every pregnant woman infected with RuV. As gestational diabetes mellitus is a risk factor for congenital viral infections, we investigated the possible roles of hypoglycemia-related endoplasmic reticulum (ER) stress as a key factor for vertical RuV infection using immortalized human first-trimester trophoblasts. Low-glucose stress was induced prior to RuV infection by culturing HTR-8/SVneo and Swan.71 cells in low-glucose (LG) medium for 24 h or high-glucose medium for 6 h and then LG medium for an additional 18 h. Clinically isolated RuV was inoculated at a multiplicity of infection of 5 to 10. The intracellular localization of the RuV capsid protein was investigated 24 to 48 h post-infection (pi) with flow cytometry (FCM) analysis and fluorescence microscopy. Viral progeny production was monitored by FCM analysis. Increases in RuV infection in LG-induced ER-stressed trophoblasts were observed. No significant increase in apoptosis of RuV-infected cells was noted at days 2 and 5 pi, and substantial viral progeny production was observed until day 5 pi. An approximate fivefold increase in viral binding was noted for the LG-stressed cells. Although the detailed mechanisms underlying viral entry into LG-stressed cells are not known and require further investigation, these findings suggest that a certain degree of LG stress in early pregnancy may facilitate infection and cause CRS.